Mechanical evaluation of electrospun poly(ε-caprolactone) single fibers. (September 2020) - Alexeev, Dmitriy; Goedecke, Nils; Snedeker, Jess; Ferguson, Stephen
Graphical abstract: Abstract: In the scope of biomechanical applications of electrospun polymer microfibers, a new method for testing single electrospun microfibers was used to reliably establish mechanical properties of poly(ε-caprolactone) microfibers within a wide range of diameters from 0.4–6.0 μm. Cyclic mechanical tests were used to establish a bimodal linear relationship between fiber diameter and Young's modulus. An inflection point was found at approximately 0.9 μm, where a sharp increase in modulus below this diameter was observed. The abrupt rise in modulus was not observed on the same scale in scaffolds produced with corresponding fibers and could not be explained only through a change in crystallinity of the polymer. Furthermore, the elastically recovered strain was assessed at maximum strain up to 20 %. It was found that polycaprolactone exhibits a viscoelastic range up to 13.17 ± 3.1 % after preconditioning, which is sufficient for most relevant biomechanical applications.